The formation of consumers' warmth and competence impressions of corporate brands: The role of corporate associations. Issue 4 (2nd March 2022) - Gidaković, Petar; Zabkar, Vesna
Abstract: Despite a growing body of evidence showing how consumers' impressions of corporate brands' warmth and competence lead to managerially relevant outcomes, the cognitive processes by which consumers form such impressions remain poorly understood. This study draws on theories from the cognitive and social psychology fields to develop a conceptual model that explains the formation of differentiated (i.e., nonstereotypical) warmth and competence impressions based on specific dimensions of corporate associations. These impressions transform consumers' information about a company into trust. The conceptual model was tested in a randomized between‐subjects experiment that manipulated the different dimensions of corporate associations and established the causal and mediating relationships (Study 1). To increase the external validity of Study 2, the participants rated real companies using a survey. The implications of the findings for consumer impression formation theory are discussed, and managerial recommendations for both influencing warmth and competence impressions and fostering consumer trust are provided.